2010
DOI: 10.1177/0885066610377968
|View full text |Cite
|
Sign up to set email alerts
|

Management of Aminoglycosides in the Intensive Care Unit

Abstract: Antibacterial resistance is increasing throughout the world, while the development of new agents is slowly progressing. In addition, the increasing prevalence of fluoroquinolone resistance may force many practitioners to choose an aminoglycoside agent in gram-negative regimens. Aminoglycosides are bactericidal agents with potent activity against gram-negative infections and activity against gram-positive infections when added to a cell wall active antimicrobial-based regimen. These agents may be dosed multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 140 publications
(171 reference statements)
0
23
0
2
Order By: Relevance
“…Although some authors have reported combining a very high AMK regimen (50 mg/kg) with high-flow CRRT to obtain adequate C peak /MIC and rapidly reduce drug concentrations below the threshold of potential toxicity [24], this approach needs to be further validated and the choice of another antimicrobial should be considered for strains with MICs 8 to 16 mg/L. Finally, we calculated drug regimens according to IBW/ABW and adjusted dose for underweight (BMI <18) or obese (BMI >28) patients [18,25]. Taccone et al .…”
Section: Discussionmentioning
confidence: 99%
“…Although some authors have reported combining a very high AMK regimen (50 mg/kg) with high-flow CRRT to obtain adequate C peak /MIC and rapidly reduce drug concentrations below the threshold of potential toxicity [24], this approach needs to be further validated and the choice of another antimicrobial should be considered for strains with MICs 8 to 16 mg/L. Finally, we calculated drug regimens according to IBW/ABW and adjusted dose for underweight (BMI <18) or obese (BMI >28) patients [18,25]. Taccone et al .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to frequently serving as primary antibiotics in developing countries, aminoglycosides are commonly used in industrialized nations against potentially life-threatening sepsis in infants, urinary tract infections with complications, intra-abdominal infections, and osteomyelitis; or as alternate drugs in cases of antibacterial resistance, for example in the world-wide prevalence of fluoroquinolone resistance (Radigan, et al, 2010). The United States Food and Drug Administration has approved nine aminoglycosides for clinical use: gentamicin, tobramycin, amikacin, streptomycin, neomycin, kanamycin, paromomycin, netilmicin and spectinomycin.…”
Section: Therapeutic Characteristicsmentioning
confidence: 99%
“…This result confirms the importance of PK variability in ICU patients due to critical illness itself, the use of extracorporeal therapies, the course of the infection, etc. (18,36). Regarding the risk of AG-induced toxicity, as gentamicin clearance is reduced in hemodialyzed patients, C 24 values were significantly higher than the recommended threshold at 24 h (30), requiring a longer dosage interval.…”
Section: Discussionmentioning
confidence: 97%
“…For several years, data in the literature have suggested that a once-daily dosing regimen is as effective as the conventional multiple daily dosing regimen but reduces toxicity associated with AG therapy (15). Monitoring of AG concentrations facilitates appropriate dosing in order to prevent underdosing and therapeutic failure, as well as overdosing and toxicity (16)(17)(18). However, many antibiotic regimens that have been developed for noncritically ill patients are likely to be inappropriate in the ICU population (19).…”
mentioning
confidence: 99%
See 1 more Smart Citation